Di-(2-ethylhexyl) phthalate substitutes accelerate human adipogenesis through PPARγ activation and cause oxidative stress and impaired metabolic homeostasis in mature adipocytes. (June 2022) - Schaffert, Alexandra; Karkossa, Isabel; Ueberham, Elke; Schlichting, Rita; Walter, Katharina; Arnold, Josi; Blüher, Matthias; Heiker, John T.; Lehmann, Jörg; Wabitsch, Martin; Escher, Beate I.; von Bergen, Martin; et al.
Graphical abstract: Highlights: 20 plasticizers and their metabolites were screened for PPARγ interaction. Metabolites of DINCH, DINP, and DPHP most potently induced human adipogenesis. These metabolites enhanced adipogenesis and PPARγ markers similar to rosiglitazone. Both compound groups caused oxidative stress and dysfunction in mature adipocytes. The observed effects are similar to high fat diet-induced adipose tissue impairment. Abstract: The obesity pandemic is presumed to be accelerated by endocrine disruptors such as phthalate-plasticizers, which interfere with adipose tissue function. With the restriction of the plasticizer di-(2-ethylhexyl)-phthalate (DEHP), the search for safe substitutes gained importance. Focusing on the master regulator of adipogenesis and adipose tissue functionality, the peroxisome proliferator-activated receptor gamma (PPARγ), we evaluated 20 alternative plasticizers as well as their metabolites for binding to and activation of PPARγ and assessed effects on adipocyte lipid accumulation. Among several compounds that showed interaction with PPARγ, the metabolites MINCH, MHINP, and OH-MPHP of the plasticizers DINCH, DINP, and DPHP exerted the highest adipogenic potential in human adipocytes. These metabolites and their parent plasticizers were further analyzed in human preadipocytes and mature adipocytes using cellular assays and global proteomics. In preadipocytes, the plasticizer metabolites significantly increased lipid accumulation, enhanced leptin and adipsin secretion, and upregulated adipogenesis-associated markers and pathways, in a similar pattern to the PPARγ agonist rosiglitazone. Proteomics of mature adipocytes revealed that both, the plasticizers and their metabolites, induced oxidative stress, disturbed lipid storage, impaired metabolic homeostasis, and led to proinflammatory and insulin resistance promoting adipokine secretion. In conclusion, the plasticizer metabolites enhanced preadipocyte differentiation, at least partly mediated by PPARγ activation and, together with their parent plasticizers, affected the functionality of mature adipocytes similar to reported effects of a high-fat diet. This highlights the need to further investigate the currently used plasticizer alternatives for potential associations with obesity and the metabolic syndrome.